Anthropometric and power attributes discriminate between national and state level male basketball players - Dalbo, V. J.; Wen, N.; Pyne, D. B.; Spiteri, T.; Guy, J. H.; Scanlan, A. T. (Journal of Australian Strength and Conditioning, 2017)
Higher level basketball players are purportedly more powerful than lower level players. However, it is unclear whether players in higher levels of basketball are more powerful as a function of being older than lower level players as past investigations failed to control for player age. We quantified anthropometric measures and power attributes across an age-matched sample of national and state level under 20 (U20) year old male basketball players.